Peer Effects on Real-Time Search Behavior in Experimental Stock Markets - Jin, Xuejun; Zhou, Xue; Yang, Xiaolan; Lin, Yiyang (Frontiers in Psychology, 2021)
It is a well-documented phenomenon that individuals stop searching earlier than predicted by the optimal, risk-neutral stopping rule, leading to inefficient searches. Individuals’ search behaviors during the process of making investment decisions in financial markets can be easily affected by their peers. In this study, we designed a search game in a simplified experimental stock market in which subjects were required to search for the best sell prices for their stocks. By randomly assigning subjects into pairs and presenting them with real-time information on their peers’ searches, we investigated the effects of peers’ decisions on search behaviors. The results showed that two subjects in the same group with real-time peer information learned from each other and engaged in similar search behaviors. However, this peer effect did not exist when subjects had access to feedback information on the ex-post best response. In addition, we found that the presence of information about peers’ decisions alone had no significant impact on search efficiency, whereas access to both information on peers’ decisions and feedback information significantly improved subjects’ search efficiency.